Analysis of the problems of Thai students in the University of the Philippines during the academic year 1971-1972 - Tipawan, Senachai 1944- (s.n.], 1972)
The purpose of the study is to identify and analyze the problems of Thai students enrolled in the University of the Philippines during the academic year 1971-1972. The study provides guidelines for the planning and implementation of a more responsive guidance program and academic services for Thai students in the University of the Philippines. It will also serve as a springboard for future studies about Thai students, or other international students, and the different aspects of campus or college life which they will encounter in this country.